Bolus ileus-an occasional cause of small bowel obstruction-case report - Janež, Jurij (International Journal of Research in Medical Sciences, 2017)
A food bolus can be an occasional cause of small bowel obstruction. Especially older and senile patients are at higher risk for developing a bolus ileus. Certain pathological conditions are associated with a higher risk for developing a bolus ileus, such as duodenal and small bowel diverticula. In this paper is presented a case of a 68-year-old female patient with food bolus, that caused a mehanical small bowel obstruction. The abdominal computed tomography scan before surgery did not show the precise cause of intestinal obstruction. During surgery we found a big grape in the distal ileum, which was removed through enterotomy. Further postoperative course was uneventful.